Analysis of Three-Dimensional Vibration Characteristics of Single-Circle Double-Track Subway Tunnel under Moving Load. (3rd February 2021) - Dai, Chunquan; Yang, Mengying; Wang, Quanlei; Yang, Tingzhi; Jiang, Kun
Abstract : With the development of urban rail transit, subway lines are becoming more and more denser, the departure time interval is short, and the probability of subway trains meeting is high. The impact of vibration caused by double-line subway meeting on the surrounding environment cannot be ignored. Taking the typical cross-section of a single-circle double-track subway tunnel as an example, a single running scenario and three typical meeting scenarios, namely, 4 s meeting, 6 s meeting, and 8 s meeting scenarios were considered, and a track-tunnel-foundation three-dimensional ABAQUS finite element model was established. The dynamic response of monitoring points at different distances between the center of the track bed and the center line of the track was analyzed. Results showed that due to the consistent load action period, the center acceleration of the track bed increases significantly during the meeting, the main frequency of vibration and the peak value of the 1/3 octave spectrum were increased by about 5 Hz, and the vibration level at the dominant frequency was increased by about 7 dB. The center displacement of the track bed and the peak compressive strain increased significantly under the 4 s meeting and 6 s meeting working scenarios; while the 8 s meeting and 4 s single running scenarios were basically the same, only the action time was doubled. The dynamic response of the 4 working scenarios decreases with the increase of distance, and the attenuation rate gradually decreases and has gradually stabilized within 15–19 m above the vault.